Round table. Venous thromboembolism: coordinator Raúl Praderi; introduction Raúl Praderi - Praderi, Raúl (Cirugía del Uruguay, 1972)
First of all, we must thank the authorities of the 209 Uruguayan Congress of Surgery for having granted us the honor of coordinating a Round Table about this theme. We will try to do our best although it is a difficult problem, old in some respects and new in others, in the which we consider that the coordination between the internist's activity and that of the surgeon is essential.